Dėl baltų kalbų šaukšto ir skydo pavadinimų kilmės - Karaliūnas, Simas (Baltistica, 1995)
NAMES FOR SHIELD AND SPOON IN BALTIC AND THEIR ORIGINAs a recurring connection of names for shield in the Indo-European languages is that with words for „board“, properly applied to a wooden shield, Lith. skỹdas, skydà (acc. sing, skỹdą) „shield” and then-counterparts in Latvian šķīda, šķīdre „id.” seem etymologically to belong to the group of words Lith. skiedrà „chip, sliver, shingle (for roofing)”, skiedà „id.”, Latv. skaîda, skaids „chip; shingle”.Some of the North European words for spoon reflect development of a wooden spoon from a flat chip or a splinter. This development is shared also by Lith. šáukštas „spoon”, an old suffix -sta- nomen instrumenti, with regular root vowel interchange áu : ū́/u connected with Lith. šùkė „splinter; chipped place, spot”, Latv. suķe, suķis „id.”, sûce „chipped place, spot”, OInd. ṡūkaḥ, ṡūkam „awn of grain; spike of in insect”, Av. sūkā- „needle”.It is almost certain that Prussian lapinis „spoon“ is an indiginous Baltic word with connexions in Slavic and possibly Latvian.